2009
DOI: 10.1103/physrevb.80.134518
|View full text |Cite
|
Sign up to set email alerts
|

Theory of resistivity upturns in metallic cuprates

Abstract: We propose that the experimentally observed resistivity upturn of cuprates at low temperatures may be explained by properly accounting for the effects of disorder in a strongly correlated metallic host. Within a calculation of the dc conductivity using real-space diagonalization of a Hubbard model treated in an inhomogeneous unrestricted Hartree-Fock approximation, we find that correlations induce magnetic droplets around impurities, and give rise to additional magnetic scattering which causes the resistivity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
(103 reference statements)
2
16
0
Order By: Relevance
“…The low temperature upturn behavior is similar to that observed in amorphous MoGe films and granular superconductors [4,[33][34][35][36] and will dramatically affect any quantitative scaling analysis. We suggest that this is evidence of a mixed phase separating the superconducting and insulating regimes.…”
mentioning
confidence: 74%
“…The low temperature upturn behavior is similar to that observed in amorphous MoGe films and granular superconductors [4,[33][34][35][36] and will dramatically affect any quantitative scaling analysis. We suggest that this is evidence of a mixed phase separating the superconducting and insulating regimes.…”
mentioning
confidence: 74%
“…Finkelman et al [38] found the spin-related MR was linear in field, inconsistent with the Kondo scattering which gives a log B dependence. They favors the picture of antiferromagnetic magnetic droplets [39]. Recently, Naito group [72] got superconductivity in parent compounds, and the upturn could be suppressed after a two-step 'protect annealing'.…”
Section: Negative Magnetoresistancementioning
confidence: 99%
“…The origin of crossover from metallic-to insulating-behavior, (i.e. upturn of resistivity) is still in debate, which may be subject to two-dimensional (2D) weak localization [35,36], Kondo-like scattering [37], additional scattering by magnetic droplets trapped at impurity sites [38,39], or a link to antiferromagnetism [40].…”
Section: Metal-insulator Transitionsmentioning
confidence: 99%
“…The components b = {x, y, z} of the spin polarization induced by a longitudinal electric field E(i, t)x σ b (i, t) = χ b (i, ω)E(i, t) . (10) in our lattice model can be formulated within a linear response theory, where the real part of the DC magnetoelectric susceptibility is calculated by 25,26…”
Section: Current-induced Spin Torquementioning
confidence: 99%